EXPLORING STUDENTS’ POINT OF VIEW IN AUTOMATED WRITING EVALUATION FOR WRITING SKILLS - Maulida Yasirli Dafania; Dangin Dangin (Institut Pendidikan Tapanuli Selatan, 2026)
The world of education continues to advance in line with this increasingly sophisticated era. Technology has now spread into various fields of learning, including learning to write. Various applications and tools have been created to support writing skills. Among them are Chat GPT and Grammarly, which are available as AWE tools and have been widely used by students as a medium to support writing. Therefore, the purpose of this study is to explore students' views on the use of AWE in supporting writing skills. A number of previous studies have analyzed the use of AWE in writing skills, but few have tested it using a phenomenological approach, and most were conducted outside Indonesia, where students have different experiences, needs, and backgrounds. This study addresses this gap by involving eight English Education students from Mercu Buana University in Yogyakarta. This study uses a qualitative method with a phenomenological approach, in which data is obtained through a semi-structured interview process with participants focusing on seven aspects, namely usage, usefulness, empowerment, critical thinking, evaluation, challenges, satisfaction, and recommendations. Recent findings show a positive view of the use of AWE in writing skills. Students view AWE as quite useful and able to increase confidence and critical thinking. However, there are several limitations to this tool, so its use is considered less than optimal.